Effectiveness of different memory training programs on improving hyperphagic behaviors of residents with dementia: a longitudinal single-blind study - Kao CC (Dove Medical Press, 2016)
Chieh-Chun Kao,1,2 Li-Chan Lin,3 Shiao-Chi Wu,4 Ker-Neng Lin,5,6 Ching-Kuan Liu7,8 1Department of Nursing, National Yang-Ming University, Taipei, 2Department of Nursing, Ching Kuo Institute of Management and Health, Keelung, 3Institute of Clinical Nursing, 4Institute of Health and Welfare Policy, National Yang-Ming University, 5Neurological Institute, Taipei Veterans General Hospital, Taipei, 6Department of Psychology, Soochow University, Taipei, Taiwan; 7Department of Neurology, Kaohsiung Medical University Hospital, 8Department of Neurology, Faculty of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan Background: Hyperphagia increases eating-associated risks for people with dementia and distress for caregivers. The purpose of this study was to compare the long-term effectiveness of spaced retrieval (SR) training and SR training combined with Montessori activities (SR + M) for improving hyperphagic behaviors of special care unit residents with dementia. Methods: The study enrolled patients with dementia suffering from hyperphagia resident in eight institutions and used a cluster-randomized single-blind design, with 46 participants in the SR group, 49 in the SR + M group, and 45 participants in the control group. For these three groups, trained research assistants collected baseline data on hyperphagic behavior, pica, changes in eating habits, short meal frequency, and distress to caregivers. The SR and SR + M groups underwent memory training over a 6-week training period (30 sessions), and a generalized estimating equation was used to compare data of all the three groups of subjects obtained immediately after the training period and at follow-ups 1 month, 3 months, and 6 months later. Results: Results showed that the hyperphagic and pica behaviors of both the SR and SR + M groups were significantly improved (P<0.001) and that the effect lasted for 3 months after training. The improvement of fast eating was significantly superior in the SR + M group than in the SR group. The improvement in distress to caregivers in both intervention groups lasted only until the posttest. Improvement in changes in eating habits of the two groups was not significantly different from that of the control group. Conclusion: SR and SR + M training programs can improve hyperphagic behavior of patients with dementia. The SR + M training program is particularly beneficial for the improvement of rapid eating. Caregivers can choose a suitable memory training program according to the eating problems of their residents. Keywords: dementia, hyperphagia, spaced retrieval training, Montessori-based activities, longitudinal research